2017
DOI: 10.1038/s41598-017-05302-3
|View full text |Cite
|
Sign up to set email alerts
|

Rice Flowering Locus T 1 plays an important role in heading date influencing yield traits in rice

Abstract: Important role of flowering genes in enhancing grain productivity in rice has become well recognized for a number of key genes regulating the florigen production, but little has been known for the two florigen genes themselves. In this study, pleiotropism of Rice Flowering Locus T 1 (RFT1), one of the two florigen genes in rice, was firstly evaluated using near isogenic lines (NILs) carrying RFT1 alleles from the indica rice cultivars Zhenshan 97 (ZS97) and Milyang 46, respectively, and then determined by tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 39 publications
1
23
0
Order By: Relevance
“…(an expression level was not detected in our RNA-seq data) and can thus barely promote floret specification and development through this pathway (Hu et al, 2015). On the other hand, Ehd1 is repressed by OsPRR37, which results in the reduction of RFT1 and leads to the inhibition of (Gao et al, 2014;Koo et al, 2013;Li et al, 2016;Liu et al, 2015;Wei et al, 2010;Yan et al, 2011;Yan et al, 2013;Zhu et al, 2017). Our model of flowering pathways would be beneficial to choose and modify the key flowering regulators to improve rice yield in the future.…”
Section: Osprr37 Confers An Ehd1-mediated Expanded Regulation On Rimentioning
confidence: 88%
See 1 more Smart Citation
“…(an expression level was not detected in our RNA-seq data) and can thus barely promote floret specification and development through this pathway (Hu et al, 2015). On the other hand, Ehd1 is repressed by OsPRR37, which results in the reduction of RFT1 and leads to the inhibition of (Gao et al, 2014;Koo et al, 2013;Li et al, 2016;Liu et al, 2015;Wei et al, 2010;Yan et al, 2011;Yan et al, 2013;Zhu et al, 2017). Our model of flowering pathways would be beneficial to choose and modify the key flowering regulators to improve rice yield in the future.…”
Section: Osprr37 Confers An Ehd1-mediated Expanded Regulation On Rimentioning
confidence: 88%
“…This model suggests that OsPRR37 confers Ehd1 ‐mediated regulation on rice flowering pathways and that Ehd1 is the determinative factor that integrates multiple flowering signals to regulate rice flowering. Flowering genes have been frequently reported to influence rice yield (Gao et al, ; Koo et al, ; Li et al, ; Liu et al, ; Wei et al, ; Yan et al, ; Yan et al, ; Zhu et al, ). Our model of flowering pathways would be beneficial to choose and modify the key flowering regulators to improve rice yield in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The regional and seasonal adaptation is mostly determined by heading date, the productivity is measured by grain yield, and whether the product can meet the demand of end-users is mainly characterized by grain quality. A number of key genes for flowering regulation in rice have been found to play important roles in the genetic control of yield traits, including Ghd7 (Xue et al, 2008;Weng et al, 2014), DTH8/Ghd8 (Wei et al, 2010; et al, 2011), Hd1 (Zhang et al, 2012;Zhang et al, 2015;Ye et al, 2018), Ghd7.1 (Yan et al, 2013), and RFT1 (Zhu et al, 2017). On the other hand, no study has been reported for the pleiotropic effects of heading-date genes on grain quality in rice.…”
Section: Discussionmentioning
confidence: 99%
“…RFT1 protein is the florigen for promoting the flowering of rice under long-day (LD) conditions (Tsuji et al, 2011). As compared to the ZS97 allele of RFT1, the MY46 and ZH11 alleles were shown to promote heading in rice populations grown under natural LD conditions in Hangzhou (Zhu et al, 2017). Replacing a ZS97 allele by a MY46 allele in the R1 population promoted flowering by 11.63 to 15.61 days over 3 years; and replacing a ZS97 allele by a ZH11 allele promoted flowering by 3.91 and 6.12 days in the transgenic population in 2 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation